Emergence of Vulvovaginal Candidiasis among Lebanese Pregnant Women: Prevalence, Risk Factors, and Species Distribution - Nahed Ghaddar; Ali El Roz; Ghassan Ghssein; José-Noel Ibrahim (Hindawi Limited, 2019)
Objective. Candida species colonize the vagina in at least 20% of women, with rates rising to 30% during pregnancy. This study aimed at determining the prevalence and risk factors of vulvovaginal candidiasis (VVC) in pregnant women at 35-37 weeks of gestation. It also aims at finding possible correlations between VVC and vaginal colonization by other agents, such as Group B Streptococcus (GBS) and bacterial vaginosis. Methodology. Over a one-year period, high vaginal swabs were collected from pregnant women during their regular antenatal checkup in different polyclinics in Beirut and South Lebanon. Swabs were examined microscopically, cultured on Sabouraud Dextrose Agar, and Candida isolates were identified using Chromatic Candida medium and Germ Tube Test. Results. VVC was detected in 44.8% of samples, with C. glabrata (44.4%) and C. albicans (43.4%) being the most isolated species. Approximately, half of pregnant women (57.7%) were coinfected with Candida and bacterial vaginosis, while 26% of them carried simultaneously Candida spp. and GBS. No significant correlation was found between the occurrence of VVC and demographic, clinical, medical, and reproductive health characteristics of pregnant women. In contrast, participants with previous miscarriages and those being hospitalized during the past 12 months were more susceptible to develop vaginal C. krusei infection in comparison to other Candida species (p=0.0316 and p=0.0042, respectively). Conclusion. The prevalence of VVC in pregnant women is an increasing trend in our community. Therefore, routine medical examination and regular screening for candidiasis in the antenatal care program is highly recommended to manage the disease and its complications.